Ain't love a witch? eaudiobook - Cassidy, Dakota (Witchless in Seattle, 2017)
My name is Crispin Alistair Winterbottom, and I'm a British Spy . . . Or I was until my untimely, dare I say, suspicious demise. Now, I'm a ghost, living my afterlife on what I fondly call Plane Limbo. But I'm determined to return to the land of the living and while I try and figure out exactly how to do that, I spend my days with the ever delightful ex-witch, Stevie Cartwright, the only person in the world who can hear me, and her charming bat familiar, Belfry. We've seen some dark days, Stevie and I. Including, an unexpected family member attempting to steal all my worldly goods, a vengeful warlock, and plenty of murder. Yet, through it all, we've become great friends and adopted several new friends (alive and dead) along the way. So when a surprise shows up on our doorstep and claims to belong to me, our safe, happy world is bloody well turned upside down and threatens, to date, the most important relationship in my life!